Characterization of tissue inhibitor metalloproteinases in semen and their relationship with vital sperm function tests vis-à-vis fertility of breeding buffalo bulls - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S (The Indian Journal of Animal Sciences, 2016)
The present study was undertaken to separate and compare the tissue inhibitor metalloproteinases (TIMP) of seminal plasma and frozen-thawed sperm extracts from 30 buffalo bulls by immunoblotting and determine a relationship between various TIMP with post-thaw sperm function tests vis-à-vis bull fertility. Seven immunoreactive bands in seminal plasma (65, 55, 48, 33, 31, 24 and 11 kDa) and 5 in frozen-thawed spermatozoa (75, 65, 55, 24 and 16 kDa) were detected in Western blots following incubation (TIMP–140) and subsequent washing in vitro, indicating that TIMP is bound to sperm membranes. The frozen-thawed semen was evaluated for first service conception rate (FSCR), per cent HOST, acrosome reaction, viability, DNA integrity and total motility and linked to TIMP. In seminal plasma, the bulls positive for 48, 33 and 24 kDa TIMP had significantly higher FSCR (57.0 ± 2.6 vs 27.0 ± 2.4%, 55.7 ± 3.0 vs 31.3 ± 3.2% and 45.0 ± 3.8 vs 32.8 ± 4.7%, respectively) as compared to their negative counterparts. Except per cent viability, almost all seminal parameters (acrosome reaction, per cent HOST, DNA integrity and total motility) were significantly higher in bulls positive for TIMP of 48, 33, 31 and 24 kDa than in their negative contemporary mates. In frozen-thawed sperm extracts, the bulls positive for TIMP–24 had significantly higher FSCR (51.7 ± 3.7 vs 27.2 ± 3.0%), higher percentage of acrosome-reacted (55.9 ± 2.8 vs 48.9 ± 2.2%) and HOS-positive (69.2 ± 1.5 vs 65.3 ± 1.9%) spermatozoa in comparison to their negative herd mates. These results suggested that TIMP influences semen quality and subsequent fertility of buffalo bulls through inhibition of metalloprotease activity in semen.